The path from social and organizational-resources to satisfaction: The mediating role of academic-engagement and the moderating role of psychological-capital - Junça Silva, A.; Abreu, P.; Brito, S. (International Journal of Educational Management, 2022)
This study draws on the Job Demands-Resources (JD-R) model to analyze if (1) social and organizational resources impact students’ satisfaction, via academic engagement, and (2) psychological capital moderates the mediating path. To test our hypotheses, we collected data from two well-established higher education institutions, in which 840 students participated. Additionally, the results demonstrated that the indirect relationship between resources and satisfaction through academic engagement was conditional on the individual’s levels of psychological capital, in such a way that it became stronger for those who presented lower levels of psychological capital, compared to those with higher levels. The students’ satisfaction can be an indicator of the institution’s perceived quality, in addition to positioning the HEI as a healthy organization. The cross-sectional design of the study is a limitation; The students’ satisfaction levels can be an indicators of the institution’s perceived quality, in addition to positioning the HEI as a healthy organization. Thus, these conclusions can contribute to guiding the actors of higher education institutions (HEIs) in designing and promoting interventions to promote students’ satisfaction. however, the study presents some guidelines for academic and organizational practice, namely regarding the relevance of resources for increasing academic engagement and, consequently, satisfaction.